2019
DOI: 10.3389/fpsyg.2019.00859
|View full text |Cite
|
Sign up to set email alerts
|

Roar of a Champion: Loudness and Voice Pitch Predict Perceived Fighting Ability but Not Success in MMA Fighters

Abstract: Historically, antagonistic interactions have been a crucial determinant of access to various fitness-affecting resources. In many vertebrate species, information about relative fighting ability is conveyed, among other things, by vocalization. Previous research found that men's upper-body strength can be assessed from voice. In the present study, we tested formidability perception of intimidating vocalization (roars) and a short utterance produced by amateur male MMA fighters attending the amateur European Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 53 publications
3
15
0
Order By: Relevance
“…As an example, it has been shown that vocalizations with increased intensity (i.e. amplitude) and duration predicted greater perceptions of men's formidability; however, f o measured from these intimidating 'human roars' predicted only perceived fighting ability but not actual fighting success in this sample [42].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…As an example, it has been shown that vocalizations with increased intensity (i.e. amplitude) and duration predicted greater perceptions of men's formidability; however, f o measured from these intimidating 'human roars' predicted only perceived fighting ability but not actual fighting success in this sample [42].…”
Section: Introductionmentioning
confidence: 66%
“…In addition to speech, there is recent evidence that other forms of vocalization are important in human communication, and future research could consider how these vocalizations are employed in mating and competitive contexts. Such examples include grunts [71], roars [42,113], screams [114], adult cries [115], laughter [116] and singing [117]. Additionally, some copulatory vocalizations are also under conscious control, and women in particular may alter their sexual groaning to manipulate male behaviour to their advantage [118].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study whose aim was to test the potential involvement of intersexual selection on different vocal displays on a cross-cultural sample of men and women (for intrasexual selection, see Raine et al, 2018; Šebesta et al, 2019). Although we used four different vocal recordings (standardized self-presentation, singing of “Happy Birthday,” and reading and singing of the national anthem), they do not represent the full range of human speech or singing.…”
Section: Discussionmentioning
confidence: 99%
“…The production of such demanding songs could be viewed as costly signaling and therefore serve as a more reliable indicator than the relatively undemanding songs employed in this study. Moreover, future studies should also perform more fine-tuned vocal analyses to compare both singing and speech (Šebesta et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This can involve different sensory modalities. For example, facial and gestural expressions impart cues of an individual's emotional condition and likely future actions, the pitch and intensity of a scream or roar alerts us to imminent threat [1], and a gentle touch or slap on the back may provide reassurance [2]. However, while the use of such visual, acoustic and tactile social information is uncontroversial, the suggestion that humans also use body-based olfactory information for communicative purposes has historically been often met by scepticism, ambivalence or even antipathy.…”
Section: Introductionmentioning
confidence: 99%